Developing and Implementing a Community-Based Model of Care for Fibromyalgia: A Feasibility Study - Michelle Teo; Bindu Mohan; Nelly D. Oelke (Pain Research and Management)
Background. Fibromyalgia (FM) is a complex disease posing challenges for primary care providers and specialists in its management. Aim. To evaluate the development and implementation of a comprehensive, integrated, community-based model of care for FM. Methods. A mixed methods feasibility study was completed in a small urban centre in southern British Columbia, Canada. Eleven adults with FM and a team of seven health care providers (HCPs) participated in a 10-week intervention involving education, exercise, and sleep management. Monthly “team-huddle” sessions with HCPs facilitated the integration of care. Data included health questionnaires, patient interviews, provider focus group/interviews, and provider surveys. Results. Both patients and HCPs valued the interprofessional team approach to care. Other key aspects included the benefits of the group, exercise, and the positive focus of the program. Effectiveness of the model showed promising results: quality of care for chronic illness, quality of life, and sleep showed significant (P<0.05) differences from baseline to follow-up. Conclusions. Our community-based model of care for FM was successfully implemented. Further testing of the model will be required with a larger sample to determine its effectiveness, although promising results were apparent in our feasibility study.